PENGARUH PARTISIPASI PEMAKAI DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KEPUASAN PEMAKAI DALAM PENGEMBANGAN SISTEM INFORMASI AKUNTANSI - Fariyana Kusumawati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2007)
This Reseach examine influence user participation and top management motivation to user satisfaction in improvement of accountong information system: user skill as moderating variabel. This reseach is done in PT Telkon Divre V Surabaya, the sampel are 30 respondent by multiple regretion analysis.The result is 99,6% (R2) is large of influence independent variable to user satisfaction in improvement accounting information system. The result of examine H1 is user participation significant influence by user skill as moderating variable dan top management variable significant influence to user satisfaction in improvment accounting information system.